Chronic Lymphoid Leukemia Complicated with Ascites - Chemir Mamode; Patrice Beauregard; Serge Langevin; Charles-Jacques Mongeau (Canadian Journal of Gastroenterology)
Ascites are common in malignancies of the gastrointestinal tract but are rarely associated with chronic lymphoid leukemia. An unusual progression of chronic lymphoid leukemia, rapidly complicated with ascites, is presented, followed by a discussion of the causes and types of ascites found in solid and blood malignancies.